The Lazarus case : life-and-death issues in neonatal intensive care - Lantos, John D. (Medicine & culture., 2001)
In this volume, John Lantos weaves a story that captures the dilemmas of modern medical practice. He draws on his experience in neonatal medicine, paediatrics and medical ethics to explore ethical dilemmas through one poignant representative situation.